2019
DOI: 10.33751/ekol.v19i2.1648
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Spesies Dan Persebaran Fauna Anura Di Cagar Alam Dan Taman Wisata Alam Telaga Warna

Abstract: Anura includes frogs and toads, playing an important role as ecosystem quality bioindicators, as well as insect population control. Anura is very sensitive to changes in the environment, since its egg stadium. Disruption to its natural habitat, can threaten Anura's survival. This research is done in the Nature reserve area and Telaga Warna Natural Nature Park. Observations using the Visual Encounter Survey (VES) method. Analyses conducted include the calculation of the species diversity index of Shannon-Wienne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…It was found on the legume plant in the humid forests around the watershed. 2 Latest N. margaritifer research conducted in Telaga Warna Nature Reserve resulted in a single individual found in a swampy area called "Rawa Gayung", and explained that this species is only known to inhabit undisturbed forests (Setiawan et al, 2019). Our study revealed new microhabitat preferences for N. margaritifer on the coffee tree with a steep slope.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It was found on the legume plant in the humid forests around the watershed. 2 Latest N. margaritifer research conducted in Telaga Warna Nature Reserve resulted in a single individual found in a swampy area called "Rawa Gayung", and explained that this species is only known to inhabit undisturbed forests (Setiawan et al, 2019). Our study revealed new microhabitat preferences for N. margaritifer on the coffee tree with a steep slope.…”
Section: Discussionmentioning
confidence: 64%
“…One specimen was found in Central Java by the Green Community in 2012, which this study shows to be the first report in Central Java. 2 The most recent studies showed a single specimen from Telaga Warna Nature Reserve, West Java with only a single individual observed (Setiawan et al, 2019). A comprehensive study reported that this species can be found only in West Java and Central Java.…”
Section: Introductionmentioning
confidence: 99%
“…This trend leads to a decrease in the frog population, posing an increasingly significant threat to their survival (Syarif and Maulana 2018). Damage to forests or water pollution causes or even causes the loss of frogs' natural habitat (Setiawan et al 2019). According to Irham (2017), there has been a current degradation in the population of amphibian species; the number of species shortages in amphibians also began to gain in some places caused by the loss or change of habitat, contamination of substances in the waters, changes in environmental conditions as well as damage to ecosystems.…”
Section: Diversity Indexmentioning
confidence: 99%
“…The high intensity of visits to the two waterfalls can indirectly threaten the presence of amphibians. As we know, amphibians are very sensitive to changes in environmental quality, for example, water pollution, habitat loss, and climate change (Setiawan et al, 2019). While the existence of amphibians is very important for the ecosystem, this is because Amphibians play an important role in the food chain.…”
Section: Introductionmentioning
confidence: 99%